Revitalization of Rimpu Tradition Towards Instilling Religious Values in the Mbojo Tribe Community - Wahyu Amanda; Mohammad Mustari; M Samsul Hadi (Jurnal Penelitian Medan Agama, 2025)
Rimpu is a traditional attire of Mbojo women, characterized by the use of sarongs in which one is wrapped around the body and the other is looped over the head, leaving only the face visible, symbolizing modesty and religious values. This study aims to identify efforts in revitalizing the Rimpu tradition, analyze its connection to the cultivation of religious values, and examine the factors influencing this relationship. The study employs a qualitative approach using ethnographic methods, focusing on describing the cultural meaning within the Mbojo community. Data collection techniques include observation, in-depth interviews, and documentation. The results show that the revitalization of the Rimpu tradition is carried out through activities such as Village Competitions and the Rimpu Mantika Festival. Rimpu is closely related to religious values through its function as a means of covering the aurat and as a medium for moral education. Internal factors such as community awareness and external factors such as government support influence the sustainability of religious values within the tradition. These findings highlight the importance of preserving Rimpu as a medium for strengthening cultural identity and fostering religious character in society.